2009
DOI: 10.1002/bit.22247
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of the yeast antioxidant enzyme Mpr1 for enhanced activity and stability

Abstract: The budding yeast Saccharomyces cerevisiae Sigma1278b has the MPR1 gene, which confers resistance to the proline analogue azetidine-2-carboxylate (AZC). This gene encodes an N-acetyltransferase Mpr1 that detoxifies AZC, and the homologous genes have been found in many yeasts. Recently, we found that Mpr1 protects yeast cells by reducing the intracellular reactive oxygen species (ROS) levels under oxidative stresses, such as heat-shock, freezing, or ethanol treatment. Unlike the known antioxidant enzymes, Mpr1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 37 publications
(54 reference statements)
1
18
0
Order By: Relevance
“…The results showed that the remaining activity of each variant decreased with the incubation time. The half-life of the activity of Phe65Leu-Mpr1 (32.2 ± 9.0 min) was longer than that of the WT-Mpr1 (11.4 ± 4.8 min), as previously reported (12). Interestingly, Asn203Lys-Mpr1 and Asn203Arg-Mpr1 similarly exhibited 2.4-fold (27.0 ± 1.0 min) and 2.2-fold (23.8 ± 4.8 min) longer activity half-lives than WT-Mpr1.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The results showed that the remaining activity of each variant decreased with the incubation time. The half-life of the activity of Phe65Leu-Mpr1 (32.2 ± 9.0 min) was longer than that of the WT-Mpr1 (11.4 ± 4.8 min), as previously reported (12). Interestingly, Asn203Lys-Mpr1 and Asn203Arg-Mpr1 similarly exhibited 2.4-fold (27.0 ± 1.0 min) and 2.2-fold (23.8 ± 4.8 min) longer activity half-lives than WT-Mpr1.…”
Section: Resultssupporting
confidence: 86%
“…Previously, we isolated an Mpr1 variant with higher thermostability, Phe65Leu-Mpr1, by the screening from PCR random mutagenesis library of MPR1 (12). Recently, we determined the three-dimensional structure of Mpr1 by crystallographic analysis (13), and showed that the folding pattern of Mpr1 is similar to those of proteins in the Gcn5-related N-acetyltransferase (GNAT) superfamily, to which Mpr1 also belongs.…”
mentioning
confidence: 99%
“…Interestingly, the Lys63Arg variant confers higher oxidative stress tolerance than WT-Mpr1 on yeast cells. The Phe65Leu mutation enhanced the thermal stability of Mpr1 (29). In the structure of Mpr1, Phe65 is buried in the hydrophobic region (Fig.…”
Section: Discussionmentioning
confidence: 95%
“…Previously, we isolated two Mpr1 variants with higher AZC resistance (Lys63Arg, Phe65Leu) (29). Interestingly, the Lys63Arg variant confers higher oxidative stress tolerance than WT-Mpr1 on yeast cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation